2020
DOI: 10.1007/s00414-020-02412-y
|View full text |Cite
|
Sign up to set email alerts
|

Aspiration in lethal drug abuse—a consequence of opioid intoxication

Abstract: Aims The primary objective of this study was to investigate whether the fatalities of opioid abuse are not only related to respiratory depression but also as a result of other side effects such as emesis, delayed gastric emptying, a reduction of the cough reflex, and impaired consciousness leading to the aspiration of gastric contents, a finding regularly observed in drug-related deaths. Design A retrospective exploratory study analyzing heroin/morphine/methadone-related deaths submitted to court-ordered aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 53 publications
(64 reference statements)
0
8
1
Order By: Relevance
“…In a 2010–2015 study of 234 patients with opioid poisoning aspiration pneumonia in Austria,[ 15 ] morphine was the most commonly used opioid (85.5% of patients), while in our study, methadone was the most frequently abused opioid (60.4% of patients). Therefore, the most commonly used opioid may be different in various regions, with all types having the potential for causing aspiration pneumonia.…”
Section: Discussioncontrasting
confidence: 47%
“…In a 2010–2015 study of 234 patients with opioid poisoning aspiration pneumonia in Austria,[ 15 ] morphine was the most commonly used opioid (85.5% of patients), while in our study, methadone was the most frequently abused opioid (60.4% of patients). Therefore, the most commonly used opioid may be different in various regions, with all types having the potential for causing aspiration pneumonia.…”
Section: Discussioncontrasting
confidence: 47%
“…One post hoc analysis of patients receiving morphine and codeine for cough suppression suggests that sedation is unlikely to contribute to their cough-suppressing properties 194 , whereas gabapentin improved cough-specific QOL in patients with refractory cough without suppressing capsaicin cough reflex sensitivity 183 . Risk of dystussia and aspiration is likely related to dosing 195 , 196 , and some patient groups who are more prone to dystussia (such as the elderly and patients with spinal trauma or neurological disease) may be more susceptible to generalized cough suppression by centrally acting nonspecific cough therapies 197 , 198 . At least one new peripherally acting nonspecific cough therapy in clinical trial (the P2X3 antagonist, gefapixant) has been shown not to produce generalized cough suppression at therapeutic doses 148 .…”
Section: Managementmentioning
confidence: 99%
“…Opioid-related deaths can occur by aspiration of the gastric contents through emesis, delayed gastric emptying, a reduction of the cough reflex, and impaired consciousness. 61 Although the aspiration of gastric content was actually reported in one case, the presence of gastric contents in the airways often is only due to agonal regurgitation or postmortem overspill and can hardly be linked to BO use. 62 In addition, BOs were almost always used in combination with other CNS depressants such as opioids, benzodiazepines, alcohol, and barbiturates, increasing the risk of respiratory depression, cerebral edema, and pulmonary edema and congestion.…”
Section: Discussion Gap Analysis and Outlookmentioning
confidence: 99%